Il corpo come linguaggio : (La "Body - art" e storie simili) - Vergine, Lea (Milano : Giampaolo Prearo Editore, 1974)
Acconci, Vito ; Anselmo, Giovanni ; Arnatt, Keith ; Baldessari, John ; Baruchello, Gianfranco ; Ben ; Berardinone, Valentino ; Beuys, Joseph ; Broodthaers, Marcel ; Brown, Trisha ; Brus, Günter ; Bugli, Enrico ; Calzolari, Pierpaolo ; Carpi, Cioni ; Chiari, Giuseppe ; Ciam, Giorgio ; d'Hooghe, Alain ; Desiato, Giuseppe ; Fox, Terry ; de Freitas, Jole ; Fried, Howard ; Gilbert & George ; Graham, Dan ; Gruppe Zaj ; Horn, Rebecca ; Job, Enrico ; Jonas, Joan ; Journiac, Michel ; Lüthi, Urs ; Mariani, Elio ; Marioni, Tom ; Masi, Denis ; Mattiacci, Eliseo ; Mauri, Fabio ; Messager, Annette ; Mühl, Otto ; Nagasawa, Hidetoshi ; Nespolo, Ugo ; Nitsch, Hermann ; Ontani, Luigi ; Oppenheim, Dennis ; Otth, Jean ; Pacus, Stanislao ; Pane, Gina ; Patella, Luca Maria ; Penone, Giuseppe ; Pisani, Gianni ; Pisani, Vettor ; Rainer, Arnulf ; Rinke, Klaus ; Rocca, Ketty La ; Ruppersberg, Allen ; Samaras, Lucas ; Schwarzkogler, Rudolf ; Serra, Richard ; Sieverding, Katharina ; Tagliaferro, Aldo ; Trotta, Antonio ; Urban, Janos ; Vaccari, Franco ; Zaza, Michele
Italiaans & Engels
boek